Two new asexual genera and six new asexual species in the family Microthyriaceae (Dothideomycetes, Ascomycota) from China - Min Qiao (Pensoft Publishers, 2021)
The family Microthyriaceae is represented by relatively few mycelial cultures and DNA sequences; as a result, the taxonomy and classification of this group of organisms remain poorly understood. During the investigation of the diversity of aquatic hyphomycetes from southern China, several isolates were collected. These isolates were cultured and sequenced and a BLAST search of its LSU sequences against data in GenBank revealed that the closest related taxa are in the genus Microthyrium. Phylogenetic analyses, based on the combined sequence data from the internal transcribed spacers (ITS) and the large subunit (LSU), revealed that these isolates represent eight new taxa in Microthyriaceae, including two new genera, Antidactylaria gen. nov. and Isthmomyces gen. nov. and six new species, Antidactylaria minifimbriata sp. nov., Isthmomyces oxysporus sp. nov., I. dissimilis sp. nov., I. macrosporus sp. nov., Triscelophorus anisopterioideus sp. nov. and T. sinensis sp. nov. These new taxa are described, illustrated for their morphologies and compared with similar taxa. In addition, two new combinations are proposed in this family.